Exposure to Vicarious Social Defeat Stress and Western-Style Diets During Adolescence Leads to Physiological Dysregulation, Decreases in Reward Sensitivity, and Reduced Antidepressant Efficacy in Adulthood - Sial, Omar K.; Gnecco, Tamara; Cardona-Acosta, Astrid M.; Vieregg, Emily; Cardoso, Ernesto A.; Parise, Lyonna F.; Bolaños-Guzmán, Carlos A. (Frontiers in Neuroscience, 2021)
A dramatic increase in the prevalence of major depression and diet-related disorders in adolescents has been observed over several decades, yet the mechanisms underlying this comorbidity have only recently begun to be elucidated. Exposure to western-style diet (WSD), high in both fats (45% kcal) and carbohydrates (35% kcal): e.g., high fat diet (HFD), has been linked to the development of metabolic syndrome-like symptoms and behavioral dysregulation in rodents, as similarly observed in the human condition. Because adolescence is a developmental period highlighted by vulnerability to both stress and poor diet, understanding the mechanism(s) underlying the combined negative effects of WSDs and stress on mood and reward regulation is critical. To this end, adolescent male C57 mice were exposed to vicarious social defeat stress (VSDS), a stress paradigm capable of separating physical (PS) versus psychological/emotional (ES) stress, followed by normal chow (NC), HFD, or a separate control diet high in carbohydrates (same sucrose content as HFD) and low in fat (LFD), while measuring body weight and food intake. Non-stressed control mice exposed to 5 weeks of NC or HFD showed no significant differences in body weight or social interaction. Mice exposed to VSDS (both ES and PS) gain weight rapidly 1 week after initiation of HFD, with the ES-exposed mice showing significantly higher weight gain as compared to the HFD-exposed control mice. These mice also exhibited a reduction in saccharin preference, indicative of anhedonic-like behavior. To further delineate whether high fat was the major contributing factor to these deficits, LFD was introduced. The mice in the VSDS + HFD gained weight more rapidly than the VSDS + LFD group, and though the LFD-exposed mice did not gain weight as rapidly as the HFD-exposed mice, both the VSDS + LFD- and VSDS + HFD-exposed mice exhibited attenuated response to the antidepressant fluoxetine. These data show that diets high in both fats and carbohydrates are responsible for rapid weight gain and reduced reward sensitivity; and that while consumption of diet high in carbohydrate and low in fat does not lead to rapid weight gain, both HFD and LFD exposure after stress leads to reduced responsiveness to antidepressant treatment.